Analisis Historis Pengembangan Kurikulum Pendidikan Agama Islam di Indonesia - Yasmin Harahap; Opik Taufik Kurrahman; Dadan Rusmana (Journal of Creative Student Research, 2024)
This study analyzes the development of the Islamic religious education curriculum in Indonesia, looking at the changes that occur along with the dynamics of social, political, and national education policies. The purpose of this study is to understand how the Islamic religious curriculum developed from the colonial period to post-independence, as well as the factors that influenced its changes. The method used is a qualitative approach with historical analysis, covering various facts and data from books, journals, the internet, and other written literature sources. The results of the study indicate that the development of the Islamic religious education curriculum in Indonesia is influenced by political, social factors, and the development of educational needs in accordance with changes in society. This curriculum has transformed from a more theoretical approach to a more practical one, with an emphasis on the formation of character and competence of students. The implication of this study is the importance of compiling a curriculum that is responsive to the development of the times and the socio-cultural context of Indonesia to produce a generation that is knowledgeable, faithful, and has noble character.